2012
DOI: 10.1039/c2cc18115k
|View full text |Cite
|
Sign up to set email alerts
|

Design of main-chain polymers of chiral imidazolidinone for asymmetric organocatalysis application

Abstract: Main-chain polymers of chiral imidazolidinone were successfully synthesized by reaction of chiral imidazolidinone dimers with disulfonic acid. Chiral imidazolidinones were incorporated into the main-chain of the polymer by ionic bonding. These polymers could be used as polymeric chiral organocatalysts for asymmetric Diels-Alder reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…A main‐chain ionic polymer of tyrosine‐derived chiral imidazolidinone 4 was synthesized as shown in Scheme . A chiral imidazolidinone dimer 3C was prepared according to the process described in our previous report . A series of main‐chain ionic polymers 4 were synthesized by the polyaddition reaction of chiral imidazolidinone dimer with butenylene spacer 3C and a selected series of disulfonic acids 5 in a CH 2 Cl 2 /H 2 O biphasic solvent system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A main‐chain ionic polymer of tyrosine‐derived chiral imidazolidinone 4 was synthesized as shown in Scheme . A chiral imidazolidinone dimer 3C was prepared according to the process described in our previous report . A series of main‐chain ionic polymers 4 were synthesized by the polyaddition reaction of chiral imidazolidinone dimer with butenylene spacer 3C and a selected series of disulfonic acids 5 in a CH 2 Cl 2 /H 2 O biphasic solvent system.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of the chiral imidazolidinone spacer of main‐chain ionic polymers 4Ae to 4Ee on the catalytic activity has been investigated in our previous report. We found that the main‐chain polymer of chiral imidazolidinone with the butenylene spacer 4Ce exhibited excellent catalytic activity . First, the effect of the disulfonate structure on the catalytic activity was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Inspiring from nature most of the researchers concentrating on synthesis of chiral polymers for different applications. The synthetic chiral polymers elegantly combine the advantages of both chiral interfaces and traditional polymers, affording wide range of applications such as, catalysts in various kinds of asymmetric reactions, 3,4 biointerface materials, 5 PH responsive materials, 6 chiral separations, 7 chiral sensors 8 etc. In recent years, the design and synthesis of helical polymers with a controlled helixsense have attracted significant attention for its possible applications like sensing, separation of enantiomers, enantioselective catalysis etc.…”
Section: A Introductionmentioning
confidence: 99%
“…27 Pecinovsky et al developed a nanoporous heterogeneous chiral catalyst via acidinduced liquid crystal self-assembly and subsequent photopolymersiation of monomer of imidazolidinone unit. 31 Mitsudone et al also supported MacMillan catalyst on montmorillonite clay using cation exchange method. 29 Haraguchi et al used polymer supported sulphonic acid for immobilization of MacMillan catalyst by ionic interaction via ion exchange between sulfonated polymer and quaternary ammonium salt.…”
Section: Introductionmentioning
confidence: 99%